IDENTIFICATION OF FAMILY SUPPORT ON QUALITY OF LIFE OF ELDERLY WOMEN IN CINTAMULYA VILLAGE, JATINANGOR DISTRICT - Dr. Merry Wijaya., Dra., M.Kes (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
ABSTRACT Quality of life for the elderly is a functional condition of the elderly which includes healthy psychological and physical health. If the physical condition of the elderly is not healthy, various complaints of discomfort due to changes in physical, mental and social conditions in elderly women can become a burden and have an impact on the quality of life, this condition has not been realized by many individuals and families due to the lack of support from the elderly's family itself. , support from family is one of the reinforcing factors to reduce the complaints / discomfort that arise, especially those related to physical health related to the reproductive health of the elderly. The purpose of this study was to identify the type of support provided by families for the health of elderly women in Cintamulya Village, Jatinangor District. This research method is a descriptive study, with a cross sectional approach, using primary data with a questionnaire on 61 elderly women in Cintamulya Village who meet the inclusion criteria. The sampling technique was proportional sampling. Research results obtained information,73.77% of the elderly women residing in Cintamulya Village are aged 60-65 years. Most support from families for elderly women in Cintamulya Village is in the form of instrumental support, amounting to 52.46%. While From assessment, emotional and spiritual support, the most and always received support from elderly women in Cintamulya Village is in the form of emotional support as much as 67.21%. Keywords: Family Support, Reproductive Health for Elderly Women.